Resilin-mimetics as a smart biomaterial platform for biomedical applications - Rajkamal Balu (Nature Portfolio, 2021)
Advances made in synthesis and analytical techniques has allowed the exploration and mimicry of natural materials. Resilin-mimetics have emerged from this advance as a biomaterial with a range of potential applications. Here, the authors review the history and current research on resilin-mimetics, providing a future perspective.